Partitioning of europium chelate into lipid bilayer as revealed by p-terphenyl and pyrene quenching - Limanskaya, L. A.; Yudintsev, A. V.; Trusova, V. M.; Gorbenko, G. P.; Deligeorgiev, T.; Vasilev, A.; Kaloianova, S.; Lesev, N. (Biophysical Bulletin)
A fluorescence quenching method is an effective tool for obtaining important information about different properties of biophysical and biochemical systems. In the present study quenching of fluorescent probes, p-terphenyl, and pyrene by europium chelate were observed in phosphatidylcholine liposomes. Europium chelates (EC) belong to a new class of potential antitumor drugs with high cytotoxic activity. These compounds are of particular interest for biomedical investigations and diagnostics since their spectral characteristics are optimal for a decrease of light scattering in biological patterns and background signals. However, the application of such drugs in a free form is limited by their high toxicity and metabolic instability. One efficient way to increase drug efficiency is based on using different drug delivery systems such as liposomes. Highly adaptable liposome-based nanocarriers currently attract increasing attention, because of their advantages, viz. complete biodegradability, ability to carry both hydrophilic and lipophilic payloads and protect them from chemical degradation and transformation, increased therapeutic index of a drug, flexibility in coupling with targeting and imaging ligands, improved pharmacodynamic profiles compared to free drugs, etc. The present study was focused on the examination of the lipid bilayer interactions of europium chelate (here referred to as V10). Fluorescence intensity of membrane incorporated probes – pyrene and p-terphenyl – was found to decrease with increasing concentration of the drug, suggesting that V10 represents an effective quencher for these probes. This finding was explained by the drug penetration into the hydrophobic membrane core, followed by the collision between V10 and probe molecules and subsequent fluorescence quenching. The acquired fluorescence quenching data were quantitatively interpreted in terms of the dynamic quenching model.